The utility of the rapid emergency medicine score (REMS) compared with SIRS, qSOFA and NEWS for Predicting in-hospital Mortality among Patients with suspicion of Sepsis in an emergency department - Onlak Ruangsomboon (2022)
Background: Many early warning scores (EWSs) have been validated to prognosticate adverse outcomes secondary to sepsis in the Emergency Department (ED). These EWSs include the Systemic Inflammatory Response Syndrome criteria (SIRS), the quick Sequential Organ Failure Assessment (qSOFA) and the National Early Warning Score (NEWS). However, the Rapid Emergency Medicine Score (REMS) has never been validated for this purpose. We aimed to assess and compare the prognostic utility of REMS with that of SIRS, qSOFA and NEWS for predicting mortality in patients with suspicion of sepsis in the ED. Methods: We conducted a retrospective study at the ED of Siriraj Hospital Mahidol University, Thailand. Adult patients suspected of having sepsis in the ED between August 2018 and July 2019 were included. Their EWSs were calculated. The primary outcome was all-cause in-hospital mortality. The secondary outcome was 7-day mortality. Results: A total of 1622 patients were included in the study; 457 (28.2%) died at hospital discharge. REMS yielded the highest discrimination capacity for in-hospital mortality (the area under the receiver operator characteristics curves (AUROC) 0.62 (95% confidence interval (CI) 0.59, 0.65)), which was significantly higher than qSOFA (AUROC 0.58 (95%CI 0.55, 0.60); p = 0.005) and SIRS (AUROC 0.52 (95%CI 0.49, 0.55); p < 0.001) but not significantly superior to NEWS (AUROC 0.61 (95%CI 0.58, 0.64); p = 0.27). REMS was the best EWS in terms of calibration and association with the outcome. It could also provide the highest net benefit from the decision curve analysis. Comparison of EWSs plus baseline risk model showed similar results. REMS also performed better than other EWSs for 7-day mortality. Conclusion: REMS was an early warning score with higher accuracy than sepsis-related scores (qSOFA and SIRS), similar to NEWS, and had the highest utility in terms of net benefit compared to SIRS, qSOFA and NEWS in predicting in-hospital mortality in patients presenting to the ED with suspected sepsis.